Victim support and the welfare state - Gallo, Carina (Victims, culture and society, 2019)
Introduction -- The golden age of the welfare state -- The end of social-democratic hegemony -- A welfare state in transformation -- A welfare state in times of crisis -- A hibernated welfare state -- Marketization and Europeanization of the welfare state -- Victim support and the state in close alliance.